Limb apraxia in multiple sclerosis - Rapaić, Dragan; Medenica, Veselin; Kozomora, Ružica; Ivanović, Lidija (Vojnosanitetski pregled, 2014)
Background/Aim. There are almost no studies on apraxia in people with multiple sclerosis. Although the white matter is damaged in MS, it is not the only location in which the pathological changes are present. Demyelinated lesions in the cortex have recently been recognized as important components of multiple sclerosis pathology. The aim of this study was to determine whether apraxia is present among people with MS, and the importance of demographic characteristics and impairment of functional systems at conceptualization and execution of movements. Methods. The experimental group consisted of 30 patients, mean age 51.34 ± 7.70 years. The patients in the experimental group were diagnosed with MS according to the McDonald criteria. The control group consisted of 30 healthy subjects, mean age 50.30 ± 10.47 years. For research purposes, we used the following instruments: Questionnaire for Collecting Demographic Data, Kurtzke Functional Systems Scores, Waterloo-Sunnybrook Apraxia Battery (WatAB). Execution of motion tasks that are a part of the WatAB were incorporated in the System for the Observation and Analysis of Motor Behavior. Results. Our study showed that limb apraxia was common in people with MS. Apraxia was present during pantomime in 26.70% of the patients, and during the imitation of movements in 44.80% of the patients. Gender, age, education level, duration of disease and a form of MS did not determine the quality of conceptualization and execution of movements. The time elapsed from the last exacerbation was a determinant of quality of executed movements. Impairments of functional systems predicted impairments of movement execution. The expanded disability scale score correlated with the severity of apraxia. Conclusion. Our study confirm the presence of apraxia in MS. It is necessary to carry out further studies using functional magnetic resonance imaging, as well as the conduct longitudinal studies to determine the precise structure of motor behavior in people with MS.